2021
DOI: 10.3389/fvets.2021.663988
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Enteromorpha Polysaccharides Supplementation Improves Breast Muscle Yield and Is Associated With Modification of mRNA Transcriptome in Broiler Chickens

Abstract: The present study evaluated the effects of dietary supplementation of Enteromorpha polysaccharides (EP) on carcass traits of broilers and potential molecular mechanisms associated with it. This study used RNA-Sequencing (RNA-Seq) to detect modification in mRNA transcriptome and the cognate biological pathways affecting the carcass traits. A total of 396 one-day-old male broilers (Arbor Acres) were randomly assigned to one of six dietary treatments containing EP at 0 (CON), 1000 (EP_1000), 2500 (EP_2500), 4000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Similar results were found by Wu et al [53] and Liu et al [54]. The ADP has been suggested to have immunomodulatory properties [27,55,56], and the current study showed that the addition of ADP ameliorated the elevation of proinflammatory cytokine (TNF-α and IL-1β) expression and inhibited IκBα degradation and NF-κB p65 activation. Supporting findings were reported by Zhang et al [57], who found that dietary ADP could improve the immune response of heatstressed broilers.…”
Section: Immune Response In Duodenumsupporting
confidence: 91%
“…Similar results were found by Wu et al [53] and Liu et al [54]. The ADP has been suggested to have immunomodulatory properties [27,55,56], and the current study showed that the addition of ADP ameliorated the elevation of proinflammatory cytokine (TNF-α and IL-1β) expression and inhibited IκBα degradation and NF-κB p65 activation. Supporting findings were reported by Zhang et al [57], who found that dietary ADP could improve the immune response of heatstressed broilers.…”
Section: Immune Response In Duodenumsupporting
confidence: 91%
“…E. prolifera polysaccharides (EP) are made up of α-and β-(1, 4)-linked monosaccharides (rhamnose, xylose, and glucuronic acid) (13), where the sulfate group is attached at the C-3 position of rhamnose (14). Recent studies indicated increased production performance, breast muscle yield, egg quality, antioxidant capacity, and intestinal morphology of chickens fed seaweed polysaccharides (15)(16)(17)(18). In addition, EP supplementation increased the weight and differentially regulates the gene expression at the transcriptome level in the bursa of Fabricius of Arbor Acres chickens (19).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the application of antibiotics for growth promotion in farm animals was banned entirely in the European Union since 2000 and in South Korea and Japan after 2011 (41). Recently, China also completely banned the preventive antibiotics for promoting the growth performance of animals to mitigate the deleterious consequences of AMR to public health and encouraged research on alternatives to preventive antibiotics (42)(43)(44)(45). Nevertheless, in large-scale aquaculture, the extensive use of therapeutic antibacterial drugs induced the AMR issues and was still a major concern.…”
Section: Discussionmentioning
confidence: 99%